Own Gender, Sibling’s Gender, Parent’s Gender - Grigoryeva, Angelina (American Sociological Review, 2017)
Research on the gender division of family labor largely focuses on housework and childcare in spousal couples. This article advances scholarship by examining the gender division of elderly parent care in sibling groups. Using the Health and Retirement Study, a nationally representative survey of elderly Americans, I find that caregiving to elderly parents varies not only by an adult child’s own gender, but also by the gender of the siblings with whom caregiving is shared and by the gender of the parent to whom care is provided. The salience of an adult child’s gender manifests in two primary ways: not only do daughters provide more care than do sons to their elderly parents, but daughters’ caregiving is also more elastic with respect to their own and their parents’ attributes than is sons’ caregiving. With respect to the gender of the siblings, sons provide relatively less care if they have sisters, whereas daughters provide relatively more care if they have brothers. With respect to the gender of the parent, sons provide relatively more care to fathers, and daughters provide relatively more care to mothers. Finally, analyses did not reveal changes over time.